2010
DOI: 10.1093/toxsci/kfq149
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Diminishes Testicular Gametogenesis, Steroidogenesis, and Steroidogenic Acute Regulatory Protein Expression in Adult Albino Rats: Possible Influence on Pituitary Gonadotropins and Alteration of Testicular Antioxidant Status

Abstract: The present study was done to evaluate the pituitary-testicular activities of rats subjected to chronic nicotine treatment. The testicular key androgenic enzymes activities, plasma and intratesticular testosterone (ITT) concentrations, and plasma concentration of gonadotropin were significantly reduced by nicotine treatment along with the decreased sperm counts and the disruption of spermatogenesis indicated by significant reduction in the number of different generations of germ cells at stage VII of the sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
94
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 44 publications
18
94
0
1
Order By: Relevance
“…Similarly, the notion that all EDCs act by mimicking oestrogen (environmental oestrogens) is too simplistic. The current literature illustrates that EDCs can act as oestrogens, anti-oestrogens, anti-androgens, steroidogenic enzyme inhibitors and can also act via interaction with the thyroid hormones and their receptors, or within the brain and the hypothalamo-pituitary axis, as well as the immune system (Fisher, 2004;Jana et al, 2006;2010a). Reports of declining sperm counts over the past 50 years and other disturbing trends alerted scientists to the possibility that exposure to chemicals in the environment may damage male reproductive health (Carlsen et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the notion that all EDCs act by mimicking oestrogen (environmental oestrogens) is too simplistic. The current literature illustrates that EDCs can act as oestrogens, anti-oestrogens, anti-androgens, steroidogenic enzyme inhibitors and can also act via interaction with the thyroid hormones and their receptors, or within the brain and the hypothalamo-pituitary axis, as well as the immune system (Fisher, 2004;Jana et al, 2006;2010a). Reports of declining sperm counts over the past 50 years and other disturbing trends alerted scientists to the possibility that exposure to chemicals in the environment may damage male reproductive health (Carlsen et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence from animal studies that perinatal exposure to nicotine results in oxidative stress and/or decreased antioxidant potential in the offspring (Bruin et al 2008, Xiao et al 2011, Conceicao et al 2015, suggesting that increased oxidative stress may be a potential mechanism underlying deleterious nicotine-induced reproductive outcomes. Indeed, adult animals exposed to nicotine exhibited increased ROS production and oxidative damage in the testes, which was associated with testicular damage and decreased sperm counts (Jana et al 2010, Mosbah et al 2015. Interestingly, the testicular pathology caused by nicotine exposure in the adult animals (e.g., degeneration of seminiferous tubules, germ cell exfoliation, loss of Leydig cells, and disrupted spermatogenesis) (Jana et al 2010, Mosbah et al 2015 are remarkably similar to the histological results in the testes of male offspring who were exposed to nicotine in utero (Lagunov et al 2011, Paccola et al 2014, suggesting a common underlying mechanism.…”
Section: Cellular Mechanisms Underlying Adverse Nicotine-induced Reprmentioning
confidence: 99%
“…Indeed, adult animals exposed to nicotine exhibited increased ROS production and oxidative damage in the testes, which was associated with testicular damage and decreased sperm counts (Jana et al 2010, Mosbah et al 2015. Interestingly, the testicular pathology caused by nicotine exposure in the adult animals (e.g., degeneration of seminiferous tubules, germ cell exfoliation, loss of Leydig cells, and disrupted spermatogenesis) (Jana et al 2010, Mosbah et al 2015 are remarkably similar to the histological results in the testes of male offspring who were exposed to nicotine in utero (Lagunov et al 2011, Paccola et al 2014, suggesting a common underlying mechanism. The relationship between nicotine, oxidative stress, and ovarian physiology has been less well studied, although nicotine has been shown to cause oxidative stress in Chinese Hamster Ovary cells (Yildiz et al 1998, Yildiz 2004.…”
Section: Cellular Mechanisms Underlying Adverse Nicotine-induced Reprmentioning
confidence: 99%
“…Ultrastructural analysis revealed that in nicotine-treated rats, germ cells and junctional specialization between Sertoli cells were degenerated; collagen fibres under the irregular basal lamina increased; acrosomes were irregular and abnormally configured [5]. Cigarette smoke is a complex mixture of over 3,000 chemicals [6], among which nicotine is regarded as a major agent mediating the detrimental effects of smoking on male fertility [7][8][9]. Nicotine exposure reduces the weight of the testis, the number of spermatocytes and spermatids, and the testosterone levels, probably through its influence on pituitary gonadotropins and testicular antioxidant status, as nicotine is a central nervous system (CNS) depressor that can inhibit the neural stimulus essential for the release of pituitary gonadotropins.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine exposure reduces the weight of the testis, the number of spermatocytes and spermatids, and the testosterone levels, probably through its influence on pituitary gonadotropins and testicular antioxidant status, as nicotine is a central nervous system (CNS) depressor that can inhibit the neural stimulus essential for the release of pituitary gonadotropins. Besides, nicotine also contributes to reactive oxygen species (ROS) generation in testis [9][10][11]. Therefore, those 2 aspects can be regarded as 2 targets for treatment of male reproductive damages induced by nicotine.…”
Section: Introductionmentioning
confidence: 99%